The Implementation of English Program to Improve the Students’ Language Skills at MA Bilingual Batu - Fitrotul Ainiyah; Munawwir Hadiwijaya (ANFA MEDIATAMA, 2023)
This study was aimed to describe the form of English program, the implementation, the supporting factors and inhibiting factors in implementing English Program at MA Bilingual Batu. This study used descriptive qualitative research with case study approach. The research mused some techniques, such as observation, in depth interview, and documentation. Then all data were analyzed by reduction technique, presentation, and conclusion. The finding of the study showed that: first, the form of English program is local subject which designed and developed by own teachers without government curriculums. Associated with the result of improvement of students’ language skills, in general is quite good and improve. Second, the implementation of English Program at MA Bilingual Batu is divided into three, they are planning (syllabus from the vice principle of linguistics), learning implementation day, and the evaluation. Third The supporting factors in implementing English Program are competent teachers, the mission, vision and the facilities of the school, and the high students’ motivation. The inhibiting factors in implementing English Program are uneven student ability and lack of consistency in using English.